2015
DOI: 10.3109/10428194.2015.1023799
|View full text |Cite
|
Sign up to set email alerts
|

NPM-RAR binding to TRADD selectively inhibits caspase activation, while allowing activation of NFκB and JNK

Abstract: The t(5;17) variant of acute promeylocytic leukemia (APL) expresses a fusion of nucleophosmin (NPM) with the retinoic acid receptor alpha (RARA). We have previously shown that NPM-RAR is a binding partner of the tumor necrosis factor receptor type-I –associated DEATH domain protein TRADD. Binding of TNF to its receptor, TNFR1, induces recruitment of TRADD, and subsequent recruitment of a cascade of proteins that ultimate activate caspase 3, NFκB , and JNK. We have previously shown that NPM-RAR interaction with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 31 publications
0
5
0
Order By: Relevance
“…In variant APL, NPM1-RARA bind to RARE as homodimers or as heterodimers with RXR, then recruited the co-repressor and exhibited one dominate negative effect on RARA to promote the leukemogenesis of variant APL, which was quite similar to PML-RARA [ 50 ]. In addition, NPM1-RARA could bind to TRADD to inhibit caspase activation and activate NF-κB as well as JNK signaling pathway [ 51 , 52 ], while NPM1-RARA could decrease the TP53 expression and then impaired its transcriptional activity [ 53 ]. Similar to PML-RARA, NPM1-RARA generated one ATRA-sensitive variant APL [ 42 , 44 ].…”
Section: Rara Rearrangement In Variant Aplmentioning
confidence: 99%
“…In variant APL, NPM1-RARA bind to RARE as homodimers or as heterodimers with RXR, then recruited the co-repressor and exhibited one dominate negative effect on RARA to promote the leukemogenesis of variant APL, which was quite similar to PML-RARA [ 50 ]. In addition, NPM1-RARA could bind to TRADD to inhibit caspase activation and activate NF-κB as well as JNK signaling pathway [ 51 , 52 ], while NPM1-RARA could decrease the TP53 expression and then impaired its transcriptional activity [ 53 ]. Similar to PML-RARA, NPM1-RARA generated one ATRA-sensitive variant APL [ 42 , 44 ].…”
Section: Rara Rearrangement In Variant Aplmentioning
confidence: 99%
“…The translocation t(5;17)(q35;q21), occurring in acute promyelocytic leukemia, generates the aberrant protein NPM-RAR, a fusion of NPM with the retinoic acid receptor  (RAR). It has been shown that NPM-RAR binds to TRADD and inhibits caspase activation, while preserving NF-κB and JNK signaling [114]. The translocation t(2;5)(p23;q35) associated with anaplastic large cell lymphoma generates a fusion protein from NPM and anaplastic lymphoma kinase (NPM-ALK).…”
Section: Nucleophosminmentioning
confidence: 99%
“…AM580 causes a significant inhibition on the growth of endometrial cancer and breast tumor,13,14 that indicates RARα as a target in the therapeutic intervention of cancer. Research points out at a crucial involvement of RARα in several cancers including CRC, breast cancer, leukemia, as well as, gastric cancer via several pathways such as ERα, p38α MAPK, G protein alpha Q, Glycogen synthase kinase 3, beta/beta-catenin, nuclear factor kappa B and c-Jun N-terminal kinase 1517. RARα is highly expressed in CRC tissues,18 however, the possibility of metastasis to be modulated by RARα to affect the progression of CRC is yet not established.…”
Section: Introductionmentioning
confidence: 99%